Maximizing energy efficiency in the process industries using pinch analysis - Abdul Manan, Zainuddin (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Efforts to increase plant energy efficiency have intensified with the recent increase in fuel price and the global concern on environmental emissions. As new processes and technologies emerge, existing processes are under pressure to increase efficiency and to maintain profitability in order to remain competitive. Many existing installations have focused on energy efficiency upgrading in order to increase profitability. Energy efficiency measures employed in the local industries are generally confined to the employment of good housekeeping techniques and the upgrading of utility systems (i.e., boilers, steam systems, chillers, hot oil circuit, refrigeration and cooling systems). Very few companies are willing to venture deep into process operations to further reduce energy consumption. As a result, benefits that can be derived from a retrofit project can be very limited. The advent of Pinch Technology provides a comprehensive as well as systematic approach to maximise a plant's energy efficiency. This paper briefly reviews the key principles of Pinch Technology and highlights the results of Pinch Analysis studies conducted on the local industries to maximize the energy efficiency.